2018
DOI: 10.1002/jctb.5537
|View full text |Cite
|
Sign up to set email alerts
|

Process for production and purification of lethal toxin neutralizing factor (LTNF) from E. coli and its economic analysis

Abstract: The developed process is able to produce purified rLTNF with 78±2% recovery. The study shows that recombinant technology can be used to produce rLTNF cost effectively and shows potential as a substitute for currently available antivenoms against snakebite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 43 publications
0
8
0
9
Order By: Relevance
“…The production of lethal toxin‐neutralizing factor (LTNF) by Escherichia coli ( E. coli ) was chosen for implementation. LTNF is a peptide purified from opossum ( Didelphis virginiana ) serum, which neutralizes snake venom and acts against toxins from insects, plant, and bacteria; it is used primarily as antivenom for snakebites . The air supply and substrate feeding pump were shut down to mimic the utility failure (accidental shutdown) of actuators often encountered in process operation to determine how the controller responds to these disruptions and how well the process recovers based on control action.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of lethal toxin‐neutralizing factor (LTNF) by Escherichia coli ( E. coli ) was chosen for implementation. LTNF is a peptide purified from opossum ( Didelphis virginiana ) serum, which neutralizes snake venom and acts against toxins from insects, plant, and bacteria; it is used primarily as antivenom for snakebites . The air supply and substrate feeding pump were shut down to mimic the utility failure (accidental shutdown) of actuators often encountered in process operation to determine how the controller responds to these disruptions and how well the process recovers based on control action.…”
Section: Introductionmentioning
confidence: 99%
“…LTNF is a peptide purified from opossum (Didelphis virginiana) serum, which neutralizes snake venom and acts against toxins from insects, plant, and bacteria; it is used primarily as antivenom for snakebites. [25][26][27] The air supply and substrate feeding pump were shut down to mimic the utility failure (accidental shutdown) of actuators often encountered in process operation to determine how the controller responds to these disruptions and how well the process recovers based on control action. Through this study, we investigated the window of opportunity that is created by employing an advanced controller when disruptions caused by utility failure occur during process operation.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the first 15 amino acids of the N-terminal sequence of the full protein have been found to contain the activity of the complete protein . From a digest of the LTNF protein, it has been reported that the N-terminal portion (10–15 amino acids) of the protein maintained the potency of the full protein when administered to mice. , The short peptide LKAM­DPTP­PLW with 11 amino acid residues from the N-terminal of the native LTNF protein has been produced recombinantly by our group and is henceforth referred to as rLTNF . We have previously demonstrated the activity of rLTNF against rattlesnake venom and proposed a manufacturing process with economic analysis. , …”
mentioning
confidence: 99%
“…The need for fast and reliable methods for monitoring cleavage reactions is prevalent in many areas of biologics manufacturing. An RP-HPLC method for monitoring the cleavage of rLTNF concatemer into monomer has been published previously . Cation exchange elute of rLTNF concatemer was treated with α-chymotrypsin to induce cleavage at the C-terminal of tryptophan to yield the monomer.…”
mentioning
confidence: 99%
See 1 more Smart Citation